Assessing patients' experience of integrated care: a survey of patient views in the North West London Integrated Care Pilot - Mastellos, Nikolaos (Igitur publishing, 2014)
INTRODUCTION: Despite the importance of continuity of care and patient engagement, few studies have captured patients' views on integrated care. This study assesses patient experience in the Integrated Care Pilot in North West London with the aim to help clinicians and policymakers understand patients' acceptability of integrated care and design future initiatives. METHODS: A survey was developed, validated and distributed to 2029 randomly selected practice patients identified as having a care plan. RESULTS: A total of 405 questionnaires were included for analysis. Respondents identified a number of benefits associated with the pilot, including increased patient involvement in decision-making, improved patient–provider relationship, better organisation and access to care, and enhanced inter-professional communication. However, only 22.4% were aware of having a care plan, and of these only 37.9% had a copy of the care plan. Knowledge of care plans was significantly associated with a more positive experience. CONCLUSIONS: This study reinforces the view that integrated care can improve quality of care and patient experience. However, care planning was a complex and technically challenging process that occurred more slowly than planned with wide variation in quality and time of recruitment to the pilot, making it difficult to assess the sustainability of benefits.